Great Answers to Tough Interview Questions - Yate, Martin John (London KOGAN PAGE, 2009)
With over 5 million copies sold around the world, Great Answers to Tough Interview Questions is the essential guide for all job-seekers, offering advice on writing a CV, mastering interview techniques and answering really challenging questions.
Include Index
Keywords: Employment interviewing -- Job hunting